The Effectiveness of Using the Pearson’s Correlation Coefficient for Compression Quality Assessment: Case of ECG Signals Compression with Discrete Cosine Transform - El Hanine, Mustapha; Abdelmounim, Elhassane (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
This work presents a comparative study which aims to validate the importance of using the Pearson’s Correlation Coefficient (PCC), for the first time in this field of research, as an effective parameter for quantitative measurement of Electrocardiogram (ECG) signal compression quality. The comparison with the Percent of Root mean squared Difference coefficient (PRD) was carried out using the Discrete Cosine Transform (DCT). The ECG signals of the three derivations DI, DII and DIII, used for the test, belong to five categories of patients with various pathologies, each category of which includes four patients. The obtained results, based on the morphology comparison of P waves, T waves and QRS complexes before compression and after reconstruction, showed that the range of values between 99.90% and 100% for the PCC, ensures a very good signal reconstruction quality with a Compression Ratio (CR) that could reach 16.